Speech by Y.A.B. Ketua Menteri Pulau Pinang at the MIC Seminar to be held at the Dewan Sri Pinang on Sunday 14th November 1976 at 9.30 a.m. - Lim, Chong Eu (1976)
Thank you for inviting me to this Seminar of the M.I.C. I congratulate the M.I.C. for having organised such a Seminar. I am sure that the meeting will be useful.